Psychological Safety and Academic Engagement of University Students - Quliev Yorqin Karimovich (Researchparks Publishing, 2026)
This article presents an analysis of the structural features of engagement among students of higher education institutions. It examines the concept of psychological safety in university education, its relationship with academic engagement, as well as the main factors influencing the formation of a safe educational environment. Theoretical approaches and empirical studies are analyzed, confirming that a high level of psychological safety contributes to increased academic motivation, responsibility, and participation among students. Special attention is given to the role of the teacher and interpersonal relationships within the group as key conditions for creating a trusting atmosphere.